Building Support for the Asad Regime: The Syrian Diaspora in Argentina and Brazil and the Syrian Uprising. Issue 3 (2nd July 2016) - Baeza, Cecilia; Pinto, Paulo
ABSTRACT: Brazil and Argentina are hosts to two of the largest populations of Syrian descent in Latin America. While Syrian immigrants and their descendants have usually defined their identities based on broad Arab nationalistic references, creating and affiliating themselves to Syrian-Lebanese and/or Arab institutions, the ongoing civil war in Syria has triggered an unprecedented mobilization around specifically Syrian issues. Most diasporic organizations have shown an unconditional support for the Baʽthist regime. This article aims at understanding the political mobilization of the Syrian diaspora in Argentina and Brazil, as well as unveiling how Bashar al-Asad's government has tried to build on their support.